Sugarcane Borer in Florida - D. G. Hall; Gregg S. Nuessly; Robert A. Gilbert (EDIS, 2007)
Revised! ENY-666, a 5-page illustrated fact sheet by D. G. Hall, G. S. Nuessly, and R. A. Gilbert, informs sugarcane growers about one of the most important of the above-ground pests of sugarcane in Florida.  This version is updated throughout with new illustrations, an updated and expanded section on biological control, updated chemical control table, and references. Published by the UF Department of Entomology and Nematology as part of the Sugarcane Handbook, February 2007.